Пушкин А.С.: Имя Россия. Исторический выбор 2008 - Сурат И.З. (АСТ:Астрель, 2008)
Экземпляры: (20100204) / Инвентарный номер: 45541 / Цена: 188.98 / Сис.шифр: 83.3(2Рос=Рус)1 45541 / Авт.знак: С 90 / ББК: 83.3(2Рос=Рус)1